Ventricular Diastolic Function in Normal Fetuses and Fetuses with Hb Bart's Disease Assessed by Color M-Mode Propagation Velocity using Cardio-STIC-M (Spatio-Temporal Image Correlation M-Mode) - Tongsong T. (2017)
© Georg Thieme Verlag KG Stuttgart · New York. Purpose: To determine whether ventricular diastolic dysfunction contributes to the pathogenesis of fetal cardiac failure due to fetal anemia using fetal Hb Bart's disease as a live model and cardio-STIC-M as a diagnostic tool. Materials and Methods: Color cardio-STIC volume datasets were acquired from fetuses at risk for Hb Bart's disease during 18-22 weeks of gestation and normal pregnancies and pregnancies with hydrops fetalis caused by Hb Bart's disease at 28-32 weeks. The volumes were analyzed off-line for velocity propagation (Vp) of the right and left ventricles to assess ventricular diastolic function using color cardio-STIC-M. Results: The Vp for the right and left ventricles was studied in fetuses at 18-22 weeks, including 64 normal fetuses (group 1) and 22 fetuses with Hb Bart's disease (group 2), and in fetuses at 28-32 weeks, including 22 normal fetuses (group 3) and 16 fetuses with Hb Bart's hydrops fetalis (group 4). The Vp of the fetuses in group 1 and group 2 was not significantly different. However, the Vp for the right and left ventricles in group 4 was significantly lower than in group 3 (19.02 vs. 9.78, p < 0.001; and 20.24 vs. 13.40, p < 0.001, respectively). The inter-observer variability had fair agreement with the intra-class correlation coefficient of 0.531 (95% CI 0.393-0.646, p < 0.001). Conclusion: Hydrops fetalis secondary to fetal anemia is initially caused by hypervolemia rather than ventricular diastolic dysfunction while ventricular diastolic compromise is a late occurring consequence of persistent hypervolemia, different from the mechanism of hydropic changes caused by cardiac causes.